Fungi and bacteria respond differently to changing environmental conditions within a soil profile. (October 2019) - Preusser, Sebastian; Poll, Christian; Marhan, Sven; Angst, Gerrit; Mueller, Carsten W.; Bachmann, Jörg; Kandeler, Ellen
Abstract: Contrasting environmental conditions in topsoil and subsoil determine both abundance and function of soil microbial communities, affecting carbon (C) dynamics throughout the entire soil profile. Although the response of soil microorganisms to single factors such as substrate availability or micro-climatic conditions has been frequently studied, fewer studies have focused on complex interactions between substrate availability and environmental conditions. To address this, we employed vertical soil translocations between topsoil and subsoil horizons of an acid and sandy Dystric Cambisol under European beech forest in Lower Saxony, Germany, to investigate the impact of changing habitat conditions on microbial decomposer communities. To follow microbial substrate utilization at different soil depths, we created hot spots of fresh organic matter (OM) by adding 13 C-labelled root litter. Soil samples were taken every three months over an experimental period of twelve months (June 2014 to June 2015). Generally, microbial biomass was strongly controlled by C availability throughout the profile. The importance of root litter as a microbial C source increased from topsoil to subsoil, but changes in available C sources affected fungi and bacteria differently. Fungi preferentially used root litter-derived C throughout the entire soil profile, demonstrating that limited access to preferred substrates, rather than micro-climatic conditions, was the main driver of decreasing fungal abundance with soil depth. In contrast, bacteria intensified utilization of root-derived C only in the absence of alternative C sources in the subsoil and were more strongly affected by spatial separation from C sources. Low soil moisture in combination with the highly sandy subsoil environment limited bacterial access to their substrates and, consequently, bacterial growth. In conclusion, fungal C utilization relies mainly on the quantity of recent plant-derived substrates, whereas bacterial access to substrates is additionally controlled by environmental conditions. This study indicates that limited microbial access to their heterogeneously distributed substrates may be an important factor for C accumulation and stabilization in subsoils. Highlights: Micro-climatic conditions inhibit bacterial carbon utilization in subsoil. Substrate limitation is the main driver of low fungal abundance in subsoil. Altered carbon sources with soil depth affect the microbial community structure.